Prevalence of xerostomia in patients with type 2 diabetes mellitus: a systematic review and meta-analysis - Shuqi Huang; Xin Zeng; Sicheng Deng; Sixiu He; Fan Liu (BMC Oral Health)
Abstract Background Xerostomia is a common complication associated with diabetes mellitus. However, the prevalence of xerostomia in patients with type 2 diabetes mellitus (T2DM) remains unclear. Therefore, the present study aimed to synthesize results from existing research to investigate the prevalence of xerostomia in T2DM patients. Methods A comprehensive search was conducted in November 2024 across four databases (PubMed, Scopus, Embase, and Web of Science). The search included English literature pertaining to the prevalence of xerostomia in adult patients with T2DM. Conference proceedings, reviews, and literature lacking complete data or containing other diseases affecting xerostomia prevalence were excluded. Two researchers independently assessed the quality of the included studies by using the Joanna Briggs Institute Standardized Critical Appraisal Checklist. Data analyses were performed using Stata version 18.0 software. A proportions approach was used for meta-analysis. If I 2  > 50%, a random-effects model was utilized; otherwise, a fixed-effects model was employed. The pooled estimates of prevalence were calculated through double arcsine transformation. Subgroup analyses were conducted based on study design, continent, evaluation tool, disease duration, and HbA1c. Results A total of 1355 studies were identified, of which 23 studies encompassing 2486 patients with T2DM met the inclusion criteria. The majority of these studies were small-sample analytical cross-sectional studies using questions about the subjective feeling of oral dryness to assess xerostomia. Risk assessment revealed 2 studies with high risk, 5 with medium risk, and 16 with low risk. The overall prevalence of xerostomia in T2DM patients was 42.49%(95%CI = 36.14–48.46). Subgroup analyses indicated no statistically significant differences based on study design, continent, evaluation tool, disease duration, and HbA1c level. Conclusions The lack of high-quality prevalence studies may result in inaccurate estimation of xerostomia prevalence among patients with T2DM. Future research should prioritize large-scale prevalence studies by utilizing more accurate assessment tools. Registration PROSPERO [CRD42022315150].